From circuits to behavior: Amygdala dysfunction in fragile X syndrome - Svalina, Matthew N.; Sullivan, Regina; Restrepo, Diego; Huntsman, Molly M. (Frontiers in Integrative Neuroscience, 2023)
Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by a repeat expansion mutation in the promotor region of the FMR1 gene resulting in transcriptional silencing and loss of function of fragile X messenger ribonucleoprotein 1 protein (FMRP). FMRP has a well-defined role in the early development of the brain. Thus, loss of the FMRP has well-known consequences for normal cellular and synaptic development leading to a variety of neuropsychiatric disorders including an increased prevalence of amygdala-based disorders. Despite our detailed understanding of the pathophysiology of FXS, the precise cellular and circuit-level underpinnings of amygdala-based disorders is incompletely understood. In this review, we discuss the development of the amygdala, the role of neuromodulation in the critical period plasticity, and recent advances in our understanding of how synaptic and circuit-level changes in the basolateral amygdala contribute to the behavioral manifestations seen in FXS.